2008
DOI: 10.1590/s0101-31222008000300022
|View full text |Cite
|
Sign up to set email alerts
|

Qualidade fisiológica e sanitária de sementes de Zinnia elegans Jacq. colhidas em diferentes épocas

Abstract: O objetivo do trabalho foi o de avaliar a influência de diferentes épocas de colheita na qualidade fisiológica e sanitária de sementes de zínia. As sementes zínia foram originadas de plantas semeadas em outubro de 2004, na área experimental do Departamento de Fitotecnia (UFSM). Os capítulos foram coletados manualmente e de acordo com a sua aparência em sete épocas: 17 de janeiro, 10 de fevereiro, 15 de março (coleta A), 23 de março (coleta B), 12 de abril, 10 de maio (coleta A) e 29 de maio (coleta B) do ano d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Corroborating with Pedroso et al (2008), who confirmed that starting from the proper maturation areas A and B (7,151 and 7,449 kg ha -1 ). This can be explained by the better development of the corn grains; they had a more adequate water content (14%) and ideal physiological maturation.…”
Section: Resultsmentioning
confidence: 60%
“…Corroborating with Pedroso et al (2008), who confirmed that starting from the proper maturation areas A and B (7,151 and 7,449 kg ha -1 ). This can be explained by the better development of the corn grains; they had a more adequate water content (14%) and ideal physiological maturation.…”
Section: Resultsmentioning
confidence: 60%
“…It is known that with seed physiological maturity, there is a tendency towards a reduction in physiological quality, where the deterioration rate is influenced by environmental factors, especially those predominant during the final stage of maturation (PEDROSO et al, 2008). Among the changes caused by this deterioration, the most important are the degradation and inactivation of enzymes (TAIZ; ZEIGER, 2006), a reduction in the respiration rate (FERGUSON; TEKRONY; EGLI, 1990) and the loss of cell membrane integrity (TAIZ; ZEIGER, 2006).…”
Section: Introductionmentioning
confidence: 99%